Modelling the dynamics of oscillating mountings with a pantograph structure using Simulink: A case study on ROSTA AB spring-damper elements - Dominik Koini; Eric Fimbinger (Results in Engineering)
Pantograph-structured oscillating mountings, such as the ROSTA AB series, are essential for suspending vibrating components in heavy machinery applications. Commonly used in vibratory screens and feeders, they provide high insulation efficiency through nonlinear motion and damping characteristics. However, accurately modelling their behaviour remains challenging due to complex, load-dependent response dynamics.This study presents a novel modelling approach using MathWorks Simulink’s multibody simulation framework. Rather than explicitly focusing on the three degrees of freedom (DoF) of an AB element – an impractical approach due to its complex responsiveness – the introduced method derives the AB element’s overall behaviour from its fundamental components: the rotational spring-damper (DR) elements. Each AB element consists of four such DR elements, which, when interconnected via rigid constraints, inherently produce the emergent behaviour. By respectively modelling the DR elements’ dynamic characteristics – nonlinear stiffness and damping functions for their single DoF (rotation) – and linking them within the multibody framework, the resulting model effectively reproduces the AB element’s dynamic response while significantly reducing computational costs. The model is calibrated and validated against experimental data, demonstrating strong agreement and thus suitability for effectively replicating the response behaviour under loading conditions.This first-of-its-kind modelling framework abstracts the full 3-DoF behaviour of an AB element via multibody-dynamic linkage of nonlinear 1-DoF DR subsystems, enabling accurate and computationally efficient simulation of suspension dynamics. This is particularly relevant for multiphysical and coupled analyses (such as advanced DEM–MBD), and especially beneficial for large-scale industrial applications where multiple oscillating mountings operate in parallel.